Theory into practice : unlocking the power and the potential of reflective journals - O'Connell, Timothy S.; Dyment, Janet E. (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2013)
Reflective journals have been used by post-secondary educators in a wide variety of teacher-training courses to encourage students to better understand the topics that they are studying. Reflective journals are often used in courses in which pre-service and in-service teachers are studying both the theoretical and practical aspects of the subject matter such as secondary teaching methods, language and literacy, teacher education, and outdoor education. While there are books on the market that address some facets of reflective journaling, there are no integrative books such as Reflective Journaling: Unlocking the Power and the Potential that are targeted specifically to pre-service and in-service teachers. There are few resources currently available to teachers wishing to use reflective journals that include: the theoretical underpinnings of reflection, the integration and impacts of research on the praxis of journaling in each chapter, and practical strategies for successful, fun journal writing for students. This book addresses this need by providing "full coverage" of using reflective journals as a pedagogical tool. Reflective Journaling: Unlocking the Power and the Potential includes four figures, 15 tables, 25 works of art, four cartoons, and 10 photos that enhance each chapter.